Legal Analysis of Online Foreign Exchange Buying and Selling and Stock Investment Using the Al-Qur'an Interpretation Method - Najla Tanjiyah (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2024)
This study aims to find out how the law of buying and selling foreign exchange online and stock investment through the Al-Qur'an detention method. The meaning of foreign exchange or trading is a type of trade or transaction that trades one country's currency against another country's currency (currency pair/pair) which involves the main money markets in the world for 24 hours on an ongoing basis. Stock Investment is the purchase and storage of capital shares in a capital market by investors, both individuals and companies in anticipation of income from dividends and capital gains determining the increased value of these shares. Lately, there have been many fraudulent investment cases under the pretext of buying and selling foreign exchange. This of course attracts the attention of the public to participate in buying and selling foreign exchange which in the end is detrimental to themselves. This study uses a field research method that examines problems or events that occur in society regarding the law of buying and selling foreign exchange or buying and selling shares. This type of research is a case study with a qualitative approach method. From this research, we can find out that if the law of buying and selling foreign exchange online and investing in shares is not in accordance with the Al-Qur'an and Sunnah, it is haram.